Effectiveness of tumescent solution combined with negative pressure wound therapy in traditional high ligation and stripping of the great saphenous vein. Issue 11 (March 2020) - Su, Feng; Cheng, Liu; Tong, Qiao
Abstract : Abstract: Traditional high ligation and stripping (THLS) is a routine operation for varicose veins. However, THLS is accompanied with postoperative subcutaneous ecchymosis and pain. In this current study, we aimed to explore the effect of tumescence solution (TS) combined with negative pressure wound therapy (NPWT) on the relief of subcutaneous ecchymosis and pain after THLS of great saphenous vein. A total of 180 patients receiving THLS were enrolled in group A, and 120 patients undergoing THLS and TS combined with NPWT were assigned into group B. The occurrences of subcutaneous ecchymosis and pain were recorded. Moreover, the total area of subcutaneous ecchymosis was estimated by the grid method. Visual analogue scale (VAS) score was used to assess the pain level of both groups. Preoperative characteristics were not significantly different between 2 groups. Postoperative ecchymosis occurred in 112 cases (62.2%) of group A and 41 cases (34.2%) of group B. The area of ecchymosis in group A (66.6 ± 44.5) cm 2 was larger than that in group B (25.2 ± 19.9) cm 2 . The number of patients without obvious pain in group A (57, 31.7%) was significantly less than that in group B (77, 64.2%) after operation. In addition, VAS score in group A (3.1 ± 2.6) was higher than that in group B (2.2 ± 1.9). In conclusion, the application of TS combined with NPWT in THLS can not only alleviate subcutaneous ecchymosis and pain, but also prevent the occurrence of subcutaneous ecchymosis and pain after operation. Therefore, it is conducive to postoperative recovery and is suitable for clinical application.